Single-phase computed tomography angiography sufficiently predicts outcomes after mechanical thrombectomy. Issue 5 (May 2020) - Yu, Kai-Wei; Lin, Chung-Jung; Luo, Chao-Bao; Lin, Yung-Yang; Guo, Wan-Yuo; Chang, Feng-Chi; Lee, I-Hui; Lin, Chun-Jen; Chung, Chih-Ping; Chien, Chun
Abstract : Background: Arterial collateral (AC) assessed by single-phase computed tomography angiography (CTA) or multiphase CTA has been used to predict clinical outcomes in patients undergoing mechanical thrombectomy (MT). Recently, venous opacification (VO) was proposed as another accurate image marker. This study aimed to compare the efficacy using AC and VO as predictors of MT outcome. Methods: Patients with occlusion of the proximal anterior circulation undergoing MT were included retrospectively. We assessed the AC status respectively according to different methods: modified Tan score, Miteff score in single-phase CTA, and pial arterial filling score in multiphase CTA. VO was assessed according to cortical vein opacification score. Favorable clinical outcome was defined as modified Rankin Scale 0-2 90 days after MT. Logistic regression models were established and receiver operating characteristics curve were used to determine the predictability of favorable outcome in patients with adequate AC and VO. Results: A total of 75 patients were enrolled. Adequate AC identified by modified Tan score (odds ratio, 7.3; p < 0.001), Miteff score (odds ratio, 4.5; p = 0.009), significantly predicted favorable outcome, but not adequate VO. The area under the curve was largest for adequate AC in model of modified Tan score 0.730 (95% CI, 0.60-0.86), while adequate VO showed the least area under the curve: 0.577 (95% CI, 0.43-0.73). Conclusion: We considered adequate AC in single-phase CTA could be reliable enough as an imaging marker rather than adequate VO to predict favorable outcome after MT.